Pengaruh Kompetensi dan Disiplin Kerja Terhadap Kinerja Guru di SMKN 1 Woha - Komalasari, Nila; Jaenab, Jaenab; Aryani, Feni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and analyze the influence of competence and work dicipline on teacher performance at SMKN 1 Woha. This study is a quantitative study and the type of reseach is assosiative with the population in this study being all teachers at SMKN 1 Woha. The sampling technique is purposive sampling totaling 38 PNS teachers, while the data collection technique uses observation, interviews, literature studies and questionnaires measured using a 5-point likert scale and then distributed to 38 teacher respondents who have PNS status at SMKN 1 Woha. The data analysis method used in this study is multiple linear regression analysis then analyzed using SPSS version 24 for windows. The results of this study state that: 1) There is a significant influence between competence on teacher performance at SMKN 1 Woha. 2) There is a significant influence between work discipline on teacher performance at SMKN 1 Woha. 3) There is a significant influence between competence and work discipline on teacher performance at SMKN 1 Woha.